2012
DOI: 10.3892/or.2012.2115
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Nrf2 enhances autophagy induced by temozolomide in U251 human glioma cell line

Abstract: Abstract. Glioblastoma multiforme (GBM) and oxidative stress are closely linked. Oxidative stress affects many signaling pathways and may cause the induction of autophagy. The NF-E2-related factor 2 (Nrf2)/Kelch-like ECH-associated protein 1 (Keap1) signaling pathway is the main pathway responsible for cell defense against oxidative stress and Nrf2 is a critical transcription factor related with cancer multidrug resistance. However, the relation between Nrf2 and regulation of autophagy is not well understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 40 publications
1
32
1
3
Order By: Relevance
“…Recently, it was demonstrated that NRF2 silencing in glioma cell lines inhibited cell proliferation [33], decreased cellular migration [34], and induced autophagic process [35]. Here we went further and showed that NRF2 silencing results in greater sensitivity and higher apoptosis induction upon TMZ treatment.…”
Section: Discussionmentioning
confidence: 61%
“…Recently, it was demonstrated that NRF2 silencing in glioma cell lines inhibited cell proliferation [33], decreased cellular migration [34], and induced autophagic process [35]. Here we went further and showed that NRF2 silencing results in greater sensitivity and higher apoptosis induction upon TMZ treatment.…”
Section: Discussionmentioning
confidence: 61%
“…After reaching 90% confluence, the medium was changed to DMEM containing 1% FBS for 12 h to synchronize the cells and the cells were subjected to serum starvation. Autophagy incidence was measured by quantifying the development of acidic vesicular organelles (AVOs) after AO staining (0.5 lg/mL) for 15 min at 37°C [39], and immediately determined as percentage of AO positive cells analyzed with a FACS Canto II software (BD, USA).…”
Section: Autophagy Incidence Quantified By Flow Cytometrymentioning
confidence: 99%
“…Accordingly, in other tumor entities, an increase of selective autophagy has been demonstrated that may be linked to the enhanced Nrf2 activity resulting from other amplification mechanisms 218,219. By contrast, Nrf2 has been shown to block autophagy induction by temozolomide in glioma or by mitoquinone in breast cancer cells,220,221 and a recent study demonstrated that tBHQ-mediated induction of autophagy is required for full activation of Nrf2 in hepatocytes 222. These findings point to a complex interrelation between autophagy and cellular redox control.…”
Section: Cross Talk Of Nrf2 With Oncogenic and Tumor-suppressor Pathwaysmentioning
confidence: 99%